PATIENT SAFETY AND HEALTHCARE-ASSOCIATED INFECTIONS - Mariela Yaneva - Deliverska (Peytchinski Publishing, 2011)
Healthcare-associated infections are infections caused by a wide variety of common and unusual bacteria, fungi, and viruses during the course of receiving medical care. Medical advances have brought lifesaving care to patients in need, yet many of those advances come with a risk of healthcare-associated infection. These infections related to medical care can be devastating and even deadly. As the ability to prevent healthcare-associated infections grows, these infections are increasingly unacceptable.Recent successes in healthcare-associated infections elimination have been very encouraging. Examples include sustained reduction in central line-associated bloodstream infections by 70%, simply by ensuring adherence to available guidelines. Reductions have been demonstrated for other helthcare-associated infections as well, but, much more remains to be done.Wherever patient care is provided, adherence to infection prevention guidelines is needed to ensure that all care is safe care. This includes traditional hospital settings as well as outpatient surgery centers, long-term care facilities, rehabilitation centers, and community clinics.